1993
DOI: 10.5511/plantbiotechnology1984.10.267
|View full text |Cite
|
Sign up to set email alerts
|

Plant Regeneration from Protoplasts Derived from Callus of Phalaenopsis

Abstract: The isolation, culture, and plant regeneration of protoplasts derived from callus of Phalaenopsis was established. Callus was obtained by the culture of a lateral bud on a young flower stalk. Protoplasts were isolated enzymatically from callus which was precultured on P basal medium (without coconut water (CW) and sucrose) for 30 days. The first cell division was observed after 7-10 days of culture in the basal medium supplemented with 2, 4-dichlorophenoxyacetic acid (2, 4-D) or CW. After 60 days of culture, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Sajise and Sagawa (1991) first reported embryogenic callus formation in Phalaenopsis, but they did not describe a detailed method for callus induction. Furthermore, Kobayashi et al (1993) utilized callus as the source for protoplasts and first succeeded in plant regeneration from protoplasts in Phalaenopsis, however, details for callus formation were not described. Ichihashi (1992) reported that callus-like masses were induced by culturing shoot tips of young flower stalk buds, in which excised explants were initially converted into a callus-like mass followed by development into PLBs.…”
Section: Resultsmentioning
confidence: 94%
“…Sajise and Sagawa (1991) first reported embryogenic callus formation in Phalaenopsis, but they did not describe a detailed method for callus induction. Furthermore, Kobayashi et al (1993) utilized callus as the source for protoplasts and first succeeded in plant regeneration from protoplasts in Phalaenopsis, however, details for callus formation were not described. Ichihashi (1992) reported that callus-like masses were induced by culturing shoot tips of young flower stalk buds, in which excised explants were initially converted into a callus-like mass followed by development into PLBs.…”
Section: Resultsmentioning
confidence: 94%
“…According to the Tukey test of mean separation at 95%, it was determined that the 2,4-D did not present significant statistical differences between its 3 levels evaluated (Table 2). However, the addition of the 2, 4-D to the culture media may favor the formation of protoplasts colonies, as was reported by Kobayashi et al (1993) who affirmed that 2, 4-D in culture media is essential for the regeneration of Phalaenopsis. Nonetheless, for both Zeatin and BA, significant statistical differences were observed between their levels, showing means of 0.66 for Zeatin and 0.60 for BA (Table 2).…”
Section: Regeneration and Formation Of Colonies From Protoplastsmentioning
confidence: 59%
“…In the family Orchidaceae, most studies on protoplasts have focused on the genera Dendrobium and Phalaenopsis. In 1990, the first isolation of protoplasts in Dendrobium hawaiian, using leaf tissue, was reported (Kuehnle and Nan, 1990), also involving callus and leaf tissue for Phalaenopsis species (Sajise and Sagawa, 1991;Kobayashi et al, 1993). Cells in suspension of Phalaenopsis have also been used for the isolation of protoplasts (Shrestha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(Kunitake and Mii, 1990) and Phalenopsis (Kobayashi at al., 1993). Thus, it would be necessary to examine various callus pretreatments for promotion of regeneration also in case of taro.…”
Section: Discussionmentioning
confidence: 99%